Amphiphilic polymer as well as preparation method and application thereof
By preparing an amphiphilic polymer containing a specific monomer, the problems of large amount and high cost of MPC monomers in the prior art are solved, and an ultra-low pollution interface with high biocompatibility and antifouling properties are formed on the surface of medical devices.
Patent Information
- Application Number
- CN202411518079.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-28
AI Technical Summary
The amount of MPC monomers in existing amphiphilic polymers is high, which makes the product expensive and makes it difficult to form an ultra-low pollution interface on the surface of medical devices to inhibit protein adsorption and cell adhesion.
By preparing an amphiphilic polymer including poly(ethylene glycol) methacrylate, fatty chain methacrylate, 2-methacryloyloxyethylphosphorylcholine and tris(alkylsiloxane) methacrylate, the biocompatibility and adhesion of the polymer are improved by utilizing the hydrophilicity of poly(ethylene glycol) methacrylate and the siloxane group of tri(alkylsiloxane) methacrylate.
It realizes the formation of good hydrophilic and lubricating coatings on the surface of medical devices, reduces the amount of MPC monomer, reduces the cost, and improves the biocompatibility and anti-fouling properties of the coating.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to an amphiphilic polymer, a preparation method thereof and an application thereof. Background Art
[0002] Biological contamination of medical device surfaces in contact with blood is a major problem in thrombosis. Inhibition of protein adsorption and cell adhesion can be achieved by forming an ultra-low contamination interface between blood components and the surface in contact with them.
[0003] The prior art discloses a variety of polymers that can form ultra-low pollution interfaces, among which 2-methacryloyloxyethyl phosphorylcholine (MPC) polymers, such as poly (2-methacryloyloxyethyl phosphorylcholine-co-2-butyl methacrylate) (PMB) and poly (2-methacryloyloxyethyl phosphorylcholine-co-2-lauryl methacrylate) (PMD), have an amphiphilic structure and a hydrophobic fatty chain, have good affinity with polymer materials, and can be adsorbed on the surface of the material; the phosphorylcholine group on the side chain imitates the phosphatidylcholine structure on the cell outer membrane, and can form a hydration layer on the surface, thereby inhibiting protein adsorption and cell adhesion. However, in the above polymers, the mass content of MPC units is generally above 30%, and because the MPC monomer is expensive, the product price is expensive. Summary of the invention
[0004] In view of this, the object of the present invention is to provide an amphiphilic polymer, a preparation method thereof and an application thereof. The amphiphilic polymer provided in the present application has good hydrophilicity as a medical device coating, and the amount of MPC monomer used in its structure is relatively small, and the cost is relatively low.
[0005] The present application provides an amphiphilic polymer, comprising a first repeating unit shown in formula (I), a second repeating unit shown in formula (II), a third repeating unit shown in formula (III) and a fourth repeating unit shown in formula (IV):
[0006]
[0007] In formula (I), a is an integer of 5 to 9, and R1 is H or methyl;
[0008] In formula (II), b is an integer from 1 to 8, and R2 is H or methyl;
[0009] In formula (III), R3 is H or methyl.
[0010] In some specific implementations, the mass ratio of the first repeating unit represented by formula (I), the second repeating unit represented by formula (II), the third repeating unit represented by formula (III) and the first repeating unit represented by formula (IV) is 5-20:50-70:10-30:2-5.
[0011] In some specific implementations, the mass ratio of the first repeating unit represented by formula (I), the second repeating unit represented by formula (II), the third repeating unit represented by formula (III) and the first repeating unit represented by formula (IV) is 10-15:60-65:15-20:3-4.
[0012] The present application also provides a method for preparing an amphiphilic polymer, comprising the following steps:
[0013] Dissolving the poly(ethylene glycol) methacrylate monomer represented by formula (1), the 2-methacryloyloxyethyl phosphorylcholine monomer represented by formula (3), the tri(alkylsiloxane) methacrylate monomer represented by formula (4), and an initiator in an alcohol solvent to obtain a first solution;
[0014]
[0015] In formula (1), a is an integer of 5 to 9, and R1 is H or methyl;
[0016] In formula (3), R3 is H or methyl;
[0017] Dissolving the fatty chain methacrylate monomer represented by formula (2) in a non-alcoholic organic solvent to obtain a second solution;
[0018]
[0019] In formula (2), b is an integer from 1 to 8, and R2 is H or methyl;
[0020] The first solution and the second solution are mixed to carry out polymerization reaction to obtain an amphiphilic polymer.
[0021] In some specific implementations, the mass ratio of the poly(ethylene glycol) methacrylate monomer shown in formula (1), the fatty chain methacrylate monomer shown in formula (2), the 2-methacryloyloxyethyl phosphorylcholine monomer shown in formula (3) and the tri(alkylsiloxane) methacrylate monomer shown in formula (4) is 5-20:50-70:10-30:2-5.
[0022] In some specific implementations, the mass ratio of the poly(ethylene glycol) methacrylate monomer shown in formula (1), the fatty chain methacrylate monomer shown in formula (2), the 2-methacryloyloxyethyl phosphorylcholine monomer shown in formula (3) and the tri(alkylsiloxane) methacrylate monomer shown in formula (4) is 10-15:60-65:15-20:3-4.
[0023] In some specific implementations, the alcohol organic solvent is selected from at least one of methanol, ethanol or isopropanol;
[0024] The non-alcohol organic solvent is selected from at least one of tetrahydrofuran, dimethyl sulfoxide or dimethylformamide.
[0025] In some specific implementations, the initiator is selected from azobisisobutyronitrile or benzoyl peroxide.
[0026] In some specific implementations, the polymerization reaction temperature is 60° C. to 80° C., and the time is 6 h to 24 h.
[0027] The present application also provides a medical device, comprising a medical device body and a coating formed on the surface of the medical device body, wherein the coating comprises the amphiphilic polymer described in the above technical solution or the amphiphilic polymer prepared by the method described in the above technical solution.
[0028] The present application uses poly(ethylene glycol) methacrylate monomers shown in formula (1), fatty chain methacrylate monomers shown in formula (2), 2-methacryloyloxyethyl phosphorylcholine monomers shown in formula (3) and tri(alkylsiloxane) methacrylate monomers shown in formula (4) as raw materials to prepare an amphiphilic polymer with good biocompatibility. The poly(ethylene glycol) methacrylate monomers shown in formula (1) are hydrophilic and are introduced into the polymer structure. When the coating is formed, they are distributed on the surface of the coating, which can increase the hydrophilicity of the coating. At the same time, as a buffer zone of the hydrophilic and hydrophobic interfaces, the phosphorylcholine groups can be arranged on the surface of the coating as much as possible, thereby increasing the biocompatibility of the coating, reducing the amount of MPC monomers used, and reducing costs. In addition, the long polyethylene glycol chains are distributed on the surface of the coating, so that the coating has good lubricity, can reduce friction, prevent the attachment and growth of microorganisms, and reduce the risk of infection. Moreover, the long polyethylene glycol chains have good stability, are not easily degraded or deteriorated, and can maintain their performance for a long time. Introducing the tri(alkylsiloxane) methacrylate structure shown in formula (4) into the polymer structure can enable the polymer to react with the hydroxyl group or other functional groups on the surface of the medical device during coating to form a strong chemical bond, thereby improving the adhesion of the polymer coating; moreover, the hydrolysis self-assembly cross-linking of the alkoxy group can form a network structure, which can further improve the stability and durability of the coating. DETAILED DESCRIPTION
[0029] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like to indicate directions or positional relationships are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific direction, be constructed and operated in a specific direction, and therefore should not be understood as limiting the present invention.
[0031] In addition, the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, "multiple" means two or more, unless otherwise clearly and specifically defined. In addition, the terms "installed", "connected" and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal connection of two components. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0032] The present application provides an amphiphilic polymer, comprising a first repeating unit shown in formula (I), a second repeating unit shown in formula (II), a third repeating unit shown in formula (III) and a fourth repeating unit shown in formula (IV):
[0033]
[0034] In formula (I), a is an integer of 5 to 9, and R1 is H or methyl;
[0035] In formula (II), b is an integer from 1 to 8, and R2 is H or methyl;
[0036] In formula (III), R3 is H or methyl.
[0037] The amphiphilic polymer provided in the present application includes the first repeating unit shown in formula (I), which is formed by poly (ethylene glycol) methacrylate monomer. The first repeating unit shown in formula (I) has good hydrophilicity. It is introduced into the polymer structure and can be distributed on the surface of the coating when forming the coating. On the one hand, it can increase the hydrophilicity of the coating, so that the coating has good lubricity, can reduce friction, prevent the attachment and growth of microorganisms, and reduce the risk of infection; on the other hand, the polyethylene glycol long chain can be used as a buffer zone of the hydrophilic and hydrophobic interface, which can arrange as many phosphorylcholine groups as possible on the surface of the coating, thereby reducing the amount of MPC monomers and reducing costs. Under the premise of ensuring the biocompatibility and antifouling effect of the coating. In addition, the polyethylene glycol long chain has good stability, is not easy to degrade and deteriorate, and can maintain its performance for a long time.
[0038] In some specific implementations, in the first repeating unit represented by formula (I), R1 is H or methyl, and a is an integer of 5 to 9, such as 5, 6, 7, 8, 9, etc.
[0039] The amphiphilic polymer provided in the present application includes a second repeating unit represented by formula (II), which is formed by a fatty chain methacrylate monomer. The second repeating unit represented by formula (II) is hydrophobic, has good affinity with the polymer material forming the medical device, can be adsorbed on the surface of the polymer material, and increases the adhesion of the coating.
[0040] In some specific implementations, in the first repeating unit represented by formula (II), R2 is H or methyl, and b is an integer from 1 to 8, for example, 1, 2, 3, 4, 5, 6, 7, 8, etc.
[0041] The amphiphilic polymer provided by the present application includes a third repeating unit shown in formula (III), which is formed by a 2-methacryloyloxyethyl phosphorylcholine (MPC) monomer. The third repeating unit shown in formula (III) has a phosphorylcholine group on the side chain, which can mimic the phosphatidylcholine structure on the cell outer membrane and form a hydration layer on the surface of the polymer material, thereby inhibiting protein adsorption and cell adhesion.
[0042] The amphiphilic polymer provided in the present application includes a fourth repeating unit shown in formula (IV), which is formed by a tri(alkylsiloxane)methacrylate monomer. The fourth repeating unit shown in formula (IV) has a siloxane group, which can react with a hydroxyl group or other functional groups on the surface of a polymer material to form a strong chemical bond, thereby improving the adhesion of the polymer coating; at the same time, the siloxy group can undergo hydrolysis self-assembly cross-linking to form a network structure on the surface of the polymer material, thereby improving the stability and durability of the coating.
[0043] In some specific implementations, the mass ratio of the first repeating unit represented by formula (I), the second repeating unit represented by formula (II), the third repeating unit represented by formula (III) and the first repeating unit represented by formula (IV) is 5-20:50-70:10-30:2-5, preferably 10-15:60-65:15-20:3-4.
[0044] The present application also provides a method for preparing an amphiphilic polymer, comprising the following steps:
[0045] Dissolving the poly(ethylene glycol) methacrylate monomer represented by formula (1), the 2-methacryloyloxyethyl phosphorylcholine monomer represented by formula (3), the tri(alkylsiloxane) methacrylate monomer represented by formula (4), and an initiator in an alcohol solvent to obtain a first solution;
[0046]
[0047] In formula (1), a is an integer of 5 to 9, and R1 is H or methyl;
[0048] In formula (3), R3 is H or methyl;
[0049] Dissolving the fatty chain methacrylate monomer represented by formula (2) in a non-alcoholic organic solvent to obtain a second solution;
[0050]
[0051] In formula (2), b is an integer from 1 to 8, and R2 is H or methyl;
[0052] The first solution and the second solution are mixed to carry out polymerization reaction to obtain an amphiphilic polymer.
[0053] The present application uses the poly(ethylene glycol) methacrylate monomer shown in formula (1), the fatty chain methacrylate monomer shown in formula (2), the 2-methacryloyloxyethyl phosphorylcholine monomer shown in formula (3), and the tri(alkylsiloxane) methacrylate monomer shown in formula (4) as raw materials to prepare a polymer, the structure of which is as described above, and the present application will not repeat it here. The present application has no special restrictions on the sources of the poly(ethylene glycol) methacrylate monomer shown in formula (1), the fatty chain methacrylate monomer shown in formula (2), the 2-methacryloyloxyethyl phosphorylcholine monomer shown in formula (3), and the tri(alkylsiloxane) methacrylate monomer shown in formula (4), and they can be purchased on the market.
[0054] In the present application, the poly(ethylene glycol) methacrylate monomer shown in formula (1), the 2-methacryloyloxyethyl phosphorylcholine monomer shown in formula (3), the tri(alkylsiloxane) methacrylate monomer shown in formula (4) and an initiator are dissolved in an alcohol solvent to obtain a first solution. In some specific implementations, the alcohol organic solvent is selected from at least one of methanol, ethanol or isopropanol, preferably methanol or ethanol. The present application has no special restrictions on the amount of the alcohol solvent, and the raw materials can be dissolved. The present application has no special restrictions on the dissolution method, and the raw materials are added to the solvent and dissolved to form a solution under stirring or standing conditions. In some specific implementations, the initiator is used to initiate the polymerization reaction of the monomers, and can be a thermal initiator, such as azobisisobutyronitrile or benzoyl peroxide, etc., and the present application has no special restrictions on this.
[0055] The present application dissolves the fatty chain methacrylate monomer shown in formula (2) in a non-alcoholic organic solvent to obtain a second solution. In some specific implementations, the non-alcoholic organic solvent is an organic solvent that is miscible with alcohols, such as tetrahydrofuran, dimethyl sulfoxide or dimethylformamide, etc., and the present application has no special restrictions on it. The present application has no special restrictions on the amount of the non-alcoholic organic solvent, and the raw materials can be dissolved. The present application has no special restrictions on the dissolution method, and the raw materials are added to the solvent and dissolved to form a solution under stirring or standing conditions.
[0056] After obtaining the first solution and the second solution, they are mixed and subjected to polymerization reaction to obtain an amphiphilic polymer. In some specific implementations, the mass ratio of the poly(ethylene glycol) methacrylate monomer shown in formula (1), the fatty chain methacrylate monomer shown in formula (2), the 2-methacryloyloxyethyl phosphorylcholine monomer shown in formula (3) and the tri(alkylsiloxane) methacrylate monomer shown in formula (4) is 5-20:50-70:10-30:2-5, preferably 10-15:60-65:15-20:3-4.
[0057] After the first solution and the second solution are mixed, the temperature is raised to the reaction temperature for polymerization reaction. In some specific implementations, the polymerization reaction temperature is 60° C. to 80° C., and the time is 6 h to 24 h. In some specific implementations, the polymerization reaction is carried out under magnetic stirring.
[0058] After the reaction is completed, the solvent is removed by evaporation under reduced pressure, and the obtained solid is washed with water, filtered, and dried to obtain an amphiphilic copolymer. In some specific implementations, the drying temperature is 40° C. to 60° C., preferably 50° C., and the drying time is 4 h to 7 h, preferably 6 h.
[0059] The present application also provides a medical device, comprising a medical device body and a coating formed on the surface of the medical device body, wherein the coating comprises the amphiphilic polymer described in the above technical solution or the amphiphilic polymer prepared by the method described in the above technical solution.
[0060] Specifically, the present application dissolves the amphiphilic polymer described in the above technical solution in a solvent, applies it on the surface of the medical device body, such as a medical catheter layer, and forms a coating after drying. The present application has no special restrictions on the coating method, the thickness of the coating, the drying method, etc., and methods familiar to those skilled in the art can be used.
[0061] The present application introduces poly(ethylene glycol) methacrylate and tri(alkylsiloxane) methacrylate structures into the polymer structure. When used for medical device coatings, the poly(ethylene glycol) structure is formed on the coating surface, which, on the one hand, increases the hydrophilicity and lubricity of the coating, reduces friction, prevents the attachment and growth of microorganisms, and reduces the risk of infection; on the other hand, it arranges as many phosphorylcholine groups as possible on the coating surface, improves the utilization rate of MPC, and can ensure the coating's effect of inhibiting protein adsorption and cell adhesion on the basis of reducing the amount of MPC and reducing costs; the tri(alkylsiloxane) methacrylate structure can react with hydroxyl groups or other functional groups on the surface of the medical device to improve the adhesion of the polymer coating, while the siloxane functional groups are hydrolyzed to form a network structure on the polymer surface, further improving the stability and durability of the coating.
[0062] The following is a detailed description of an amphiphilic polymer provided by the present application, its preparation method and its application in conjunction with embodiments.
[0063] Example 1
[0064] 0.1 g of poly(ethylene glycol) methacrylate (polyethylene glycol molecular weight is 300-1000), 0.05 g of 2-methacryloyloxyethyl phosphorylcholine, 0.025 g of 3-(trimethoxysilyl)propyl methacrylate and 0.01 g of benzoyl peroxide are dissolved in 5 mL of methanol to obtain a first solution; 0.325 g of octadecyl methacrylate is dissolved in 5 mL of dimethyl sulfoxide to obtain a second solution;
[0065] After the first solution and the second solution were mixed, the temperature was raised to 60°C and the mixture was stirred under magnetic stirring for 24 hours. After the reaction was completed, all the solvents were evaporated under reduced pressure, washed with pure water, filtered, and dried at 50°C for 6 hours to obtain a polymer.
[0066] Example 2
[0067] 0.025 g of m-PEG6-2-methacrylate, 0.15 g of 2-methacryloyloxyethyl phosphorylcholine, 0.01 g of 3-(triethoxysilyl)propyl methacrylate and 0.01 g of azobisisobutyronitrile were dissolved in 5 mL of ethanol to obtain a first solution; 0.315 g of lauryl methacrylate was dissolved in 5 mL of tetrahydrofuran to obtain a second solution;
[0068] After the first solution and the second solution were mixed, the temperature was raised to 80°C and the mixture was stirred under magnetic stirring for 6 hours. After the reaction was completed, all the solvents were evaporated under reduced pressure, washed with pure water, filtered, and dried at 50°C for 6 hours to obtain a polymer.
[0069] Example 3
[0070] 0.1 g of poly(ethylene glycol) methacrylate (polyethylene glycol molecular weight is 300-1000), 0.125 g of 2-methacryloyloxyethyl phosphorylcholine, 0.025 g of 3-(trimethoxysilyl)propyl methacrylate and 0.01 g of benzoyl peroxide are dissolved in 5 mL of ethanol to obtain a first solution; 0.25 g of n-butyl methacrylate is dissolved in 5 mL of tetrahydrofuran to obtain a second solution;
[0071] After the first solution and the second solution were mixed, the temperature was raised to 65°C and the mixture was stirred under magnetic stirring for 12 hours. After the reaction was completed, all the solvents were evaporated under reduced pressure, washed with pure water, filtered, and dried at 50°C for 6 hours to obtain a polymer.
[0072] Example 4
[0073] 0.07 g of poly(ethylene glycol) methacrylate (polyethylene glycol molecular weight is 300-1000), 0.095 g of 2-methacryloyloxyethyl phosphorylcholine, 0.015 g of 3-(trimethoxysilyl)propyl methacrylate and 0.01 g of azobisisobutyronitrile are dissolved in 5 mL of ethanol to obtain a first solution; 0.32 g of lauryl methacrylate is dissolved in 5 mL of dimethylformamide to obtain a second solution;
[0074] After the first solution and the second solution were mixed, the temperature was raised to 75°C and the mixture was stirred under magnetic stirring for 6 hours. After the reaction was completed, all the solvents were evaporated under reduced pressure, washed with pure water, filtered, and dried at 50°C for 6 hours to obtain a polymer.
[0075] Comparative Example 1
[0076] 0.1 g of poly(ethylene glycol) methacrylate (polyethylene glycol molecular weight is 300-1000), 0.15 g of 2-methacryloyloxyethyl phosphorylcholine and 0.01 g of benzoyl peroxide are dissolved in 5 mL of ethanol to obtain a first solution; 0.25 g of lauryl methacrylate is dissolved in 5 mL of tetrahydrofuran to obtain a second solution;
[0077] After the first solution and the second solution were mixed, the temperature was raised to 65°C and the mixture was stirred under magnetic stirring for 12 hours. After the reaction was completed, all the solvents were evaporated under reduced pressure, washed with pure water, filtered, and dried at 50°C for 6 hours to obtain a polymer.
[0078] Comparative Example 2
[0079] 0.2 g of 2-methacryloyloxyethyl phosphorylcholine, 0.02 g of 3-(trimethoxysilyl)propyl methacrylate and 0.01 g of benzoyl peroxide were dissolved in 5 mL of ethanol to obtain a first solution; 0.28 g of lauryl methacrylate was dissolved in 5 mL of tetrahydrofuran to obtain a second solution;
[0080] After the first solution and the second solution were mixed, the temperature was raised to 65°C and the mixture was stirred under magnetic stirring for 12 hours. After the reaction was completed, all the solvents were evaporated under reduced pressure, washed with pure water, filtered, and dried at 50°C for 6 hours to obtain a polymer.
[0081] Comparative Example 3
[0082] 0.225 g of poly(ethylene glycol) methacrylate (molecular weight of polyethylene glycol is 300-1000), 0.025 g of 3-(trimethoxysilyl)propyl methacrylate and 0.01 g of benzoyl peroxide are dissolved in 5 mL of ethanol to obtain a first solution; 0.25 g of lauryl methacrylate is dissolved in 5 mL of tetrahydrofuran to obtain a second solution;
[0083] After the first solution and the second solution were mixed, the temperature was raised to 65°C and the mixture was stirred under magnetic stirring for 12 hours. After the reaction was completed, all the solvents were evaporated under reduced pressure, washed with pure water, filtered, and dried at 50°C for 6 hours to obtain a polymer.
[0084] Test Example 1
[0085] Examples 1 to 4, Comparative Examples 1 to 3 and commercially available MPC polymer (PC1059, CAS: 144514-07-8) were dissolved in ethanol to prepare 1‰ solutions. Flat polycarbonate sheets were immersed in the above solutions for 10 minutes, then taken out and dried naturally, and the contact angles were tested. Then all plastic sheets were immersed in 37°C pure water for 1 day and taken out and dried naturally, and the contact angles were tested. The results are shown in Table 1, which shows the contact angles of the coatings prepared in the examples and comparative examples.
[0086] Table 1 Contact angles of coatings prepared in Examples and Comparative Examples
[0087] Before blistering at 37℃ After soaking in 37℃ water Polycarbonate Sheet 83.582° / Example 1 44.646° 87.853° Example 2 38.943° 83.582° Example 3 16.054° 32.209° Example 4 42.602° 62.868° Comparative Example 1 28.723° 71.523° Comparative Example 2 18.529° 56.487° Comparative Example 3 48.625° 84.952° Commercially available MPC polymers 46.684° 104.706°
[0089] As can be seen from Table 1, the polymer provided in the present application has a smaller contact angle as a coating after being immersed in water at 37°C, and has good hydrophilicity; moreover, the amount of MPC monomer used in the polymer provided in the present application is relatively small, which reduces the cost.
[0090] Test Example 2 Biocompatibility Test Results
[0091] According to GB / T16886.4-2022 Biological Evaluation of Medical Devices Part 4: Selection of Tests for Interaction with Blood, the indirect contact method and direct contact method were used to evaluate the potential hemolytic reaction of the samples. The conclusion was that the difference in hemolytic index between the test sample group and the negative control group was less than 2%, and the test samples were not considered to have potential hemolytic reactions.
[0092] According to GB / T16886.5-2017 Biological Evaluation of Medical Devices Part 5: In vitro Cytotoxicity Test, the cytotoxicity of the extract was evaluated. The test results showed that the cell viability of the sample extract was 94.15%, which was greater than 70%, with no potential cytotoxicity. The positive control, negative control and blank control met the quality control requirements.
[0093] The test was conducted in accordance with GB / T16886.10-2017 Biological Evaluation of Medical Devices Part 10: Irritation and Skin Sensitization Test to evaluate the skin sensitization reaction of the extract. The conclusion was that no skin sensitization reaction was found in guinea pigs after induction by the sample extract, the sensitization positive rate was 0%, and there was no evidence of skin sensitization reaction in guinea pigs.
[0094] According to GB. / T16886.10-2017 Biological Evaluation of Medical Devices Part 10: Irritation and Skin Sensitization Test, the intradermal reaction of the extract was evaluated. The conclusion was that all test animals performed normally during the test, and the immediate observation results of all injection sites were normal. The samples met the test requirements.
[0095] According to GB / T16886.11-2021 Biological Evaluation of Medical Devices Part 11: Systemic Toxicity Test, the systemic toxicity reaction of the extract was evaluated. The conclusion was that the sample extract did not cause animal death or acute systemic toxicity reaction, and the sample met the test requirements.
[0096] According to GB / T16886.3-2019 Biological Evaluation of Medical Devices Part 3: Genotoxicity, Carcinogenicity and Reproductive Toxicity Tests, the potential mutagenicity of the test samples was evaluated by bacterial reverse mutation test with and without metabolic activation system. The conclusion was that the number of reverse mutation colonies in the sample group and the negative control group was within the expected range, and the number of reverse mutation colonies in the positive control group was more than 2 times that of the negative control group. The test samples were not mutagenic to Salmonella typhimurium strains TA97a, TA98, TA100, TA102, and TA1535.
[0097] According to GB / T16886.3-2019 Biological Evaluation of Medical Devices Part 3: Genotoxicity, Carcinogenicity and Reproductive Toxicity Tests, the potential genotoxicity of the test materials to cells was evaluated, and the conclusion was that the test solution of the test article was not mutagenic to the chromosomes of Chinese hamster lung cells (CHL) with or without the addition of S9 metabolic activation substances. The positive and negative controls met the quality control requirements.
[0098] According to GB / T16886.4-2022 Biological Evaluation of Medical Devices Part 4: Selection of Tests for Interaction with Blood, the potential effects of the samples on the blood were evaluated, and the conclusion was that the test samples had no significant effect on various hematological indicators.
[0099] According to GB / T16886.4-2022 Biological Evaluation of Medical Devices Part 4: Selection of Tests for Interaction with Blood, the complement activation properties of the samples were evaluated, and the conclusion was that the test samples had no effect on complement activation.
[0100] According to GB / T16886.4-2022 Biological Evaluation of Medical Devices Part 4: Selection of Tests for Interaction with Blood, the sample is evaluated to see whether it is an activator of the endogenous coagulation system. The conclusion is that the test sample has no effect on the partial thromboplastin time.
[0101] According to GB / T16886.4-2022 Biological Evaluation of Medical Devices Part 4: Selection of Tests for Interaction with Blood, the effect of the test samples on platelet activation was evaluated, and the conclusion was that the test samples had no effect on platelet activation.
[0102] In the above test results, the samples all include the polymers prepared in Examples 1-4.
[0103] Test Example 3: Erosion Resistance Test
[0104] The polymer prepared in Example 1 was dissolved in ethanol to prepare a 1‰ solution. The oxygenator was immersed in the above solution for 10 minutes, and then taken out to dry naturally. The coating content of the oxygenator with coating was compared before and after flushing. The content was greater than 10 mg, as shown in Table 2.
[0105] Table 2 Erosion resistance test
[0106]
[0107] It can be seen from Table 2 that after the polymer provided in the present application forms a coating, the erosion resistance is good.
[0108] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An amphiphilic polymer comprising a first repeating unit represented by formula (I), a second repeating unit represented by formula (II), a third repeating unit represented by formula (III) and a fourth repeating unit represented by formula (IV): In formula (I), a is an integer of 5 to 9, and R1 is H or methyl; In formula (II), b is an integer from 1 to 8, and R2 is H or methyl; In formula (III), R3 is H or methyl.
2. The amphiphilic polymer according to claim 1, characterized in that The mass ratio of the first repeating unit represented by formula (I), the second repeating unit represented by formula (II), the third repeating unit represented by formula (III) and the first repeating unit represented by formula (IV) is 5-20:50-70:10-30:2-5.
3. The amphiphilic polymer according to claim 2, characterized in that The mass ratio of the first repeating unit represented by formula (I), the second repeating unit represented by formula (II), the third repeating unit represented by formula (III) and the first repeating unit represented by formula (IV) is 10-15:60-65:15-20:3-4.
4. A method for preparing an amphiphilic polymer, comprising the following steps: Dissolving the poly(ethylene glycol) methacrylate monomer represented by formula (1), the 2-methacryloyloxyethyl phosphorylcholine monomer represented by formula (3), the tri(alkylsiloxane) methacrylate monomer represented by formula (4), and an initiator in an alcohol solvent to obtain a first solution; In formula (1), a is an integer of 5 to 9, and R1 is H or methyl; In formula (3), R3 is H or methyl; Dissolving the fatty chain methacrylate monomer represented by formula (2) in a non-alcoholic organic solvent to obtain a second solution; In formula (2), b is an integer from 1 to 8, and R2 is H or methyl; The first solution and the second solution are mixed to carry out polymerization reaction to obtain an amphiphilic polymer.
5. The preparation method according to claim 4, characterized in that: The mass ratio of the poly(ethylene glycol) methacrylate monomer represented by formula (1), the fatty chain methacrylate monomer represented by formula (2), the 2-methacryloyloxyethyl phosphorylcholine monomer represented by formula (3) and the tri(alkylsiloxane) methacrylate monomer represented by formula (4) is 5-20:50-70:10-30:2-5.
6. The preparation method according to claim 5, characterized in that: The mass ratio of the poly(ethylene glycol) methacrylate monomer represented by formula (1), the fatty chain methacrylate monomer represented by formula (2), the 2-methacryloyloxyethyl phosphorylcholine monomer represented by formula (3) and the tri(alkylsiloxane) methacrylate monomer represented by formula (4) is 10-15:60-65:15-20:3-4.
7. The preparation method according to claim 4, characterized in that: The alcohol organic solvent is selected from at least one of methanol, ethanol or isopropanol; The non-alcohol organic solvent is selected from at least one of tetrahydrofuran, dimethyl sulfoxide or dimethylformamide.
8. The preparation method according to claim 4, characterized in that: The initiator is selected from azobisisobutyronitrile or benzoyl peroxide.
9. The preparation method according to claim 4, characterized in that: The polymerization reaction temperature is 60° C. to 80° C., and the reaction time is 6 h to 24 h.
10. A medical device, comprising a medical device body and a coating formed on the surface of the medical device body, wherein the coating comprises the amphiphilic polymer described in any one of claims 1 to 3 or the amphiphilic polymer prepared by the method described in any one of claims 4 to 9.